CeleryDB: a genomic database for celery. (9th July 2018) - Feng, Kai; Hou, Xi-Lin; Li, Meng-Yao; Jiang, Qian; Xu, Zhi-Sheng; Liu, Jie-Xia; Xiong, Ai-Sheng
Abstract: Celery ( Apium graveolens L.) is a plant belonging to the Apiaceae family, and a popular vegetable worldwide because of its abundant nutrients and various medical functions. Although extensive genetic and molecular biological studies have been conducted on celery, its genomic data remain unclear. Given the significance of celery and the growing demand for its genomic data, the whole genome of 'Q2-JN11' celery (a highly inbred line obtained by artificial selfing of 'Jinnan Shiqin') was sequenced using HiSeq 2000 sequencing technology. For the convenience of researchers to study celery, an online database of the whole-genome sequences of celery, CeleryDB, was constructed. The sequences of the whole genome, nucleotide sequences of the predicted genes and amino acid sequences of the predicted proteins are available online on CeleryDB. Home, BLAST, Genome Browser, Transcription Factor and Download interfaces composed of the organizational structure of CeleryDB. Users can search the celery genomic data by using two user-friendly query tools: basic local alignment search tool and Genome Browser. In the future, CeleryDB will be constantly updated to satisfy the needs of celery researchers worldwide. Database URL: http://apiaceae.njau.edu.cn/celerydb